PENGARUH KOMPETENSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR PERTANAHAN KABUPATEN MUSI RAWAS - Dewi Rosa Indah; Noorchamid Ustadi (Jurnal Interprof, 2018)
This study aims to determine whether there is Influence Competence Against Public Satisfaction at the Land Office of Musi Rawas Regency, Is there a Quality of Service Influence On Satisfaction Of People On Land Office Of Regency Of Musi Rawas And Is There Influence Of Competence And Quality Of Service To Satisfaction Of Community At Land Office Of Regency Of Musi Rawas. In this study the population in question is the people who deal with the Land Office of Musi Rawas Regency within a period of one month (September) as much as 521 applicants and the sample in this study were 84 respondents. To know the influence of Competence to Satisfaction Society. That is by using the IBM IBM SPSS 20.0 For Windows program obtained from t test (table 4:16) test results with tcount obtained 14.144 and sig.0,000. This means thitung> Ttable or sig.000 value smaller than the significant level (α) 0.05. The ttab value can be from db = n-1 = 84-1 = 83 which is 1.671. Thus, based on the criteria of hypothesis testing, if tcount (14.144)> ttable (1.671) means reject Ho and accept Ha, so it can be concluded that there is a significant influence Partial Competence on Satisfaction of civil servants at the Land Office of Musi Rawas Regency. To know the effect of Quality Service to Satisfaction Society That is by using IBM IBM SPSS 20.0 For Windows program obtained from t test (table 4:19) test result with tcount obtained by 10,785 and sig.0,000. This means thitung> ttable or sig.000 value is smaller than the significant level (α) 0.05. The ttab value can be from db = n-1 = 84-1 = 83 which is 1.671. Thus, based on the criteria of hypothesis testing, if tcount (10,785)> ttable (1,671) means reject Ho and accept Ha, so it can be concluded that there is significant influence of Service Quality partially to Satisfaction of civil servants at Land Office of Musi Rawas Regency. To know the influence of Competence and Quality of Service to Satisfaction Society That is byusing IBM IBM SPSS 20.0 For Windows program obtained from F test (table 4:22) test result with the value of Fhitung obtained equal to 111,676 and sig,0,000. This means Fcount> Ftable or sig.000 value is smaller than the significant level (α) 0.05. Thus, based on the criteria of hypothesis testing, if Fcount (111,676)> Ftable (3.11) means reject Ho and accept Ha, so it can be concluded that there is significant influence of Competence and Quality of Service to Satisfaction of public employee at Land Office of Musi Rawas Regency.